Fingerprint Study of Curcuma xanthorrhiza Rhizome by High Performance Thin Layer Chromatography (HPTLC) - Wikara, Tina; Sulistiowaty, Anny; Murhandini, Sri; Usia, Tepy (Jurnal Jamu Indonesia, 2016)
The rhizome of Curcuma xanthorrhiza Roxb is intensively used in Indonesia as traditional medicine. It is widely used for hepatoprotective and anti inflammatory activities. To ensure the quality of its extract, we have studied the fingerprint or phytochemical analysis. This research was aimed to produce a chromatogram profile of the rhizome by HPTLC. The HPTLC fingerprint chromatogram of C. xanthorrhiza rhizome was performed using HPTLC plate of silica gel 60 F254 as the stationary phase and chloroform-methanol (97:3) as the mobile phase. Spot detection was carried out by TLC photo documentary system at 254 and 366 nm and TLC scanner at 427 nm. The developed method was validated according to ICH guidelines by determination of specificity and precision. We found that the specifity and precission of the method were met the acceptance criteria. In conclusion, the developed method is valid and could be used for quality control and standardization of herbal medicine containing C. xanthorrhiza rhizome.